Biometrical analysis reveals major differences between the two subspecies of the European rabbit. (25th May 2015) - Ferreira, Catarina Campos; Castro, Francisca; Piorno, Vicente; Barrio, Isabel Catalán; Delibes‐Mateos, Miguel; Rouco, Carlos; Mínguez, Luis E.; Aparicio, Fernando; Blanco‐Aguiar, José A.; Ramírez, Esther; Iriarte, Candelaria; Ríos‐Saldaña, Carlos A.; et al.
<x xml:space="preserve">Abstract</x> The climatic oscillations that have occurred in the last few million years have strongly affected species distribution ranges. Highly divergent genetic lineages arose, some of which correspond to recognized subspecies that currently occupy small geographical areas. Understanding the implications of the genetic differences between these subspecies is crucial for proper conservation of Evolutionarily Significant Units. We use the two European rabbit subspecies, Oryctolagus cuniculus cuniculus and O. c. algirus, in the Iberian Peninsula as a model to investigate the repercussions at the biometric level of their largely recognized genetic differentiation. To accomplish this we analysed the ear and hind foot length, and the body mass of 999 adult rabbits from 27 locations across the distribution range of both subspecies in their native range, the Iberian Peninsula. Our results show biometric differences between the two subspecies, also explained by geographical location and sex, O. c. algirus being lighter and having shorter ear and hind foot lengths. We examine these findings under an evolutionary framework, and discuss their implications for current conservation efforts. Future research should focus on the ecological implications of these biometric differences, namely potential different habitat use and anti‐predatory strategies in the species' native range.